Tracing intermediate phases during crystallization in a Ni–Zr metallic glass. (March 2020) - Liu, S.Y.; Cao, Q.P.; Mu, X.; Xu, T.D.; Wang, D.; Ståhl, K.; Wang, X.D.; Zhang, D.X.; Kübel, C.; Jiang, J.Z.
Abstract: Crystallization of metallic glasses (MGs) is a complex dynamic process, driven by thermodynamics and limited by kinetics, which often involves phase transformation from the metastable amorphous state, via intermediates, to the final stable crystalline states. The intermediate structural state remains mysterious at present but crucial for a deeper understanding of the physics and mechanisms of the crystallization process. Detailed structural characterization of the complex intermediate crystalline phases using transmission electron microscopy (TEM) provides a unique platform to study such issues. Here, we monitor the evolution of the crystallization process for Ni65 Zr35 (at%) MG ribbon with structural heterogeneities. Direct visualization combined with compositional analysis reveal that the intermediate phase with Zr concentration higher than that of the MG consists of stacked nanometer-sized layers of Ni-rich units (Ni at% > 67%) and Ni10 Zr7 -like units, where the thin Ni-rich single layer gradually disappears with increasing annealing temperature. Our findings provide insight into the key role of Ni in the structural transition process, improving the understanding of the atomic diffusion-dominated crystallization in MGs. Graphical abstract: Image, graphical abstract